Ventilator-associated pneumonia is characterized by excessive release of neutrophil proteases in the lung - Wilkinson, Thomas S; Conway Morris, Andrew; Kefala, Kallirroi; O'Kane, Cecilia M; Moore, Norma R; Booth, Nuala A; McAuley, Daniel F; Dhaliwal, Kevin; Walsh, Timothy S; Haslett, Christopher; Sallenave, Jean-Michel; Simpson, A John (Chest, 2012)
Ventilator-associated pneumonia (VAP) is characterized by neutrophils infiltrating the alveolar space. VAP is associated with high mortality, and accurate diagnosis remains difficult. We hypothesized that proteolytic enzymes from neutrophils would be significantly increased and locally produced inhibitors of human neutrophil elastase (HNE) would be decreased in BAL fluid (BALF) from patients with confirmed VAP. We postulated that in suspected VAP, neutrophil proteases in BALF may help identify "true" VAP. BAL was performed in 55 patients with suspected VAP and in 18 control subjects. Isolation of a pathogen(s) at > 10⁴ colony-forming units/mL of BALF dichotomized patients into VAP (n = 12) and non-VAP (n = 43) groups. Matrix metalloproteinases (MMPs), HNE, inhibitors of HNE, and tissue inhibitors of matrix metalloproteinases (TIMPs) were quantified. Plasminogen activator (PA) activity was estimated by sodium dodecyl sulfate polyacrylamide gel electrophoresis and zymography. Neutrophil-derived proteases HNE, MMP-8, and MMP-9 were significantly increased in cell-free BALF from patients with VAP as compared with those without VAP (median values: HNE, 2,708 ng/mL vs 294 ng/mL, P < .01; MMP-8, 184 ng/mL vs 5 ng/mL, P < .01; MMP-9, 310 ng/mL vs 11 ng/mL, P < .01). HNE activity was also significantly increased in VAP (0.45 vs 0.01 arbitrary units; P < .05). In contrast, no significant differences were observed for protease inhibitors, TIMPs, or PAs. HNE in BALF, at a cutoff of 670 ng/mL, identified VAP with a sensitivity of 93% and specificity of 79%. Neutrophil proteases are significantly elevated in the alveolar space in VAP and may contribute to pathogenesis. Neutrophil proteases appear to have potential in suspected VAP for distinguishing true cases from "non-VAP" cases.